Thwaites Glacier grounding-line retreat: influence of width and buttressing parameterizations. Issue 220 (2014) - Docquier, David; Pollard, David; Pattyn, Frank
Abstract: Major ice loss has recently been observed along coastal outlet glaciers of the West Antarctic ice sheet, mainly due to increased melting below the ice shelves. However, the behavior of this marine ice sheet is poorly understood, leading to significant shortcomings in ice-sheet models attempting to predict future sea-level rise. The stability of a marine ice sheet is controlled by the dynamics at the grounding line, the boundary between the grounded ice stream and the floating ice shelf. One of the largest contributors to current sea-level rise is the fast-flowing Thwaites Glacier, which flows into the Amundsen Sea. Here we use an ice-stream/ice-shelf model and perform a number of experiments along a central flowline to analyze the sensitivity of its grounding line on centennial timescales. In the absence of width and buttressing effects, we find that the grounding line retreats by ˜300 km in 200 years from the present day (rate of 1.5 km a –1 ). With variable glacier width implemented in the model, flow convergence slows the retreat of Thwaites grounding line at 0.3–1.2 km a –1 . The parameterization of ice-shelf buttressing according to different observed scenarios further reduces the glacier retreat and can even lead to a slight advance in the most buttressed case.